Triggering antibacterial activity of a common plant by biosorption of selected heavy metals - Kováčová, Mária; Bodnár Yankovych, Halyna; Augustyniak, Adrian; Casas-Luna, Mariano; Remešová, Michaela; Findoráková, Lenka; Stahorský, Martin; Čelko, Ladislav; Baláž, Matej (JBIC, Journal of biological inorganic chemistry, 2024)
The presented study proposes an efficient utilization of a common Thymus serpyllum L. (wild thyme) plant as a highly potent biosorbent of Cu(II) and Pb(II) ions and the efficient interaction of the copper-laden plant with two opportunistic bacteria. Apart from biochars that are commonly used for adsorption, here we report the direct use of native plant, which is potentially interesting also for soil remediation. The highest adsorption capacity for Cu(II) and Pb(II) ions (qe = 12.66 and 53.13 mg g-1, respectively) was achieved after 10 and 30 min of adsorption, respectively. Moreover, the Cu-laden plant was shown to be an efficient antibacterial agent against the bacteria Escherichia coli and Staphylococcus aureus, the results being slightly better in the former case. Such an activity is enabled only via the interaction of the adsorbed ions effectively distributed within the biological matrix of the plant with bacterial cells. Thus, the sustainable resource can be used both for the treatment of wastewater and, after an effective embedment of metal ions, for the fight against microbes.
Keywords: Staphylococcus aureus; Adsorption; těžké kovy; antibakteriální látky; mikrobiální testy citlivosti; Lead; Microbial Sensitivity Tests; Copper; adsorpce; Thymus Plant; měď; olovo; Anti-Bacterial Agents; Thymus (rostlina); Metals, Heavy; Escherichia coli